A CMOS-MEMS cantilever sensor for capnometric applications - Mirza, A. (Institute of Electronics Information Communication Engineers, 2014)
Capnometers monitor the concentration of CO2 in exhaled breath, which can be a life saving modality. High cost, big size and high power consumption of the conventional capnometers limit their scope and adaption. To overcome these issues, a CMOS MEMS microcantilever based CO2 sensor is proposed for capnometric applications. The microcantilever is manufactured using CMOS MEMS technology and its critical parameters are analytically investigated. The optimized microcantilever has a quality factor, sensitivity and resolution of 3116, 16 mHz/ppm and 0.31 ppb, respectively. Â© IEICE 2014.